Philosophical Questions of the Relation to Goods in Antiquity and Scholastic Philosophy - Antal, Péter (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
This paper explores the early issues of the relation to goods in ancient and medieval philosophy trends. As an introduction to the topic, I examine the conditions for the emergence of Greek philosophical thinking. The paper is divided into two major sections: the first section introduces the ideas of ancient Greek philosophy on property and wealth, while the second one considers the development of the ideas of early medieval philosophy on the same topic. It should be pointed out that in ancient philosophy the subject was not given much prominence, since the concept of existence and virtue preceded the problems of property, wealth and distribution. Yet it is worth examining this period from this point of view, too, because regarding the relationship to wealth, we can find several important philosophical principles. I will present primarily the relevant medieval thoughts after discussing the relevant works of great figures of scholasticism. I will also discuss in detail the teachings of Duns Scotus, since it is primarily to him that we owe the most of his statements relevant to our subject of scholasticism. There is no doubt that the questions examined in this study are taking us closer to the definition of the content of common good. This is particularly true about Aristotle and St. Thomas, based on whose work these doctrines are also examined with distinguished attention. To sumup, we can say that questions on wealth distribution and the distribution of goods, in other words the ownership structure between the state and the individual are very much essential, since through them the content of the common good becomes tangible. The aim of my study is to support this assertion.